PENGARUH STRATEGI BAURAN PROMOSI TERHADAP VOLUME PENJUALAN JASA KONVEKSI PADA CV ANUGERAH SANDANG ABADI BANJARMASIN - Penta Lestarini Budiati; Talita Akhiria (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
Abstract, This research aims to determine whether the promotion mix consisting of advertising, sales promotion, personal selling, public relations, and direct marketing has a partial and simultaneous effect on sales volume. The population as well as the sample in this research were all resellers, amounting to 23 resellers. The method of data analysis in this study uses multiple linear regression methods with the help of the SPSS version 22.0 application. The results showed that based on a partial test only advertising, sales promotion, personal selling and direct marketing variables had a significant effect on sales volume. Meanwhile, the public relation variable does not significantly influence the sales volume at CV Anugerah Sandang Abadi in Banjarmasin. Then based on the simultaneous test, the results showed that the promotion mix consisting of advertising, sales promotion, personal selling, public relation and direct marketing variables simultaneously had a positive and significant effect on sales volume.